Genetic analysis of early maturing provitamin A maize (Zea mays L.) inbred lines under Striga infestation, combined drought and heat stress - Adeyeye, B.R. (Federal University of Technology Minna, 2023)
High yielding and stable early maturing provitamin A (PVA) maize hybrids with combined stresses (drought and heat and Striga) tolerance are needed to combat malnutrition, low yield and insecurity in sub-Sahara Africa (SSA). To address this need, PVA, PVA-QPM (quality protein maize) inbred lines with Striga and drought tolerant genetic make-up were developed through the massive effort of the International Institute of Tropical Agriculture Maize Improvement Program (IITAMIP) for its hybrid development and commercialization. This study was designed to (i) to develop early maturing PVA single cross hybrids that are tolerant to multiple stresses (combined drought and heat stress and Striga infestation), (ii) classify the set of inbred lines into heterotic groups, (iii) assess the levels of resistance/tolerance of inbred lines to Striga infestation and combined drought and heat stress tolerance in selected early maturing PVA inbred lines, (iv) identify inbred and hybrid testers, and (v) Determine the performance and yield stability of hybrids across contrasting environments. A panel of two-hundred and ten single-cross hybrids were generated from 50 selected early maturing PVA inbred lines using the Line x tester mating design crossed to four commercial PVA early maturing inbred testers plus six single crosses derived from intermating the four testers, plus four commercial checks. 250 PVA, PVA-QPM early maturing maize inbred lines plus six commercial inbred checks were evaluated under Striga infestation, combined drought and heat stress and optimal environments in Nigeria from 2019 to 2021 growing seasons. Days to 50 % anthesis and silking, plant and ear heights, plant and ear aspects complemented grain yield of the inbred lines. These inbred lines are used in their hybrid combination to produce outstanding PVA hybrids. General combining ability (GCA) and specific combining ability (SCA) mean squares were significant for grain yield and other traits indicating that additive and non-additive gene effects were important in the control of the inheritance of grain yield and other traits across the contrasting environments. Using the base indices as criteria for selection, 93 Striga resistant, 82 combined drought and heat tolerant and 36 inbred lines that combined resistance/tolerance to both stresses were identified. TZEIOR 172 x TZEIOR 108 and TZEIOR 202 x TZEI 25 has been identified as highest yielding and most stable hybrids across the three contrasting environments. TZEIOR 21 x TZEI 25 was identified as the preferred hybrid for Striga infested environments. TZEIOR 202 x TZEIOR 164 was identified as the preferred hybrid under combined drought and heat stress. The inbred line such as TZEIOR 201 and TZEIOR 202 recorded significantly positive GCA effects for grain yield across the contrasting environments could be useful for developing Striga tolerant and/or combined drought and heat tolerant hybrids and synthetic.